FACTORS INFLUENCING THE PRODUCTIVITY OF COCONUT ESTATES - T.S.G. Peiris; M.T.N. Fernando; U.P. de S. Waidayanatha (International Coconut Community, 2001)
The yield gap between the potential and actual productivity has been widening in coconut estates (>9 ha) over the years. Among many reasons, the non-adoption and incorrect adoption of recommended agronomic and crop management practices on coconut cultivation have largely contributed to this yield gap. A survey carried out by the Coconut Research Institute (CRI) indicated that the lack of competent caretakers to correctly implement the crop management practices is a major reason to the yield gap and that there is an urgent demand for trained Farm Managers. Eight percent of the estates was identified as ‘poor’ with respect to the nut yield and the standard of the management practice adopted. Majority of both proprietors and caretakers (75%) was not satisfied with the productivity of their estates. The performance of the estates was significantly associated with the land suitability class of coconut and the uses of recommend practices. About 75% of the caretakers had not received any training on coconut cultivation. According to the perception of the proprietors, males between 25-30 years of age are the best group to be trained as Farm Managers. The training course should include theory and practice on all aspects of coconut cultivation, intercropping, animal production, labour management, accounting procedures in estates, and the use of agricultural machinery.